What do you really know about Islam? - Shaykh Khalid Yasin; One Islam Productions; Saba Islamic Media ([Australia] : One Islam Productions ; Kuala Lumpur : Saba Islamic Media (distributor), 2003)
The speaker, Shaykh Khalid Yasin gives the viewer an insight into the beliefs and pillars of Islam, through which one sees that Islam is innocent from such claims. This lecture is especially useful for non-Muslims who wish to gain the proper knowledge about the religion of Islam
Title from title screen
Speaker: Shaykh Khalid Yasin
DVD format
Keywords: Islam; Islam -- Customs and practices; Religious life -- Islam